Perspectivas Actuales de la Obstetricia - Pastén M., , Jorge; Salinas P., Hugo; Naranjo D., Benjamín (Revista Hospital Clínico Universidad de Chile, 2006)
The risk to any pregnant couple of having a liveborn infant with a chromosomal abnormality or structural defect is between 3% and 5%. Though advances in fetal treatment are limited, progress in fetal evaluation has been considerable. The advances in the last years in imaging technics, genetic and invasive technics as well as a better understanding physiology of many fetal diseases and the natural history. New developments in screening strategies have, however, resulted in improved performance, which has decreased the use of prenatal diagnostic procedures substantially over the past decade. Still remains to a large extent the prevention of preterm labour, pre-eclampsia and cerebral palsy. Many fetal conditions exist for which treatment is possible and gives a good postnatal outcome. This is an option that years ago would have been denied them. Extensive discussion and parental counselling, often interdisciplinary, is the norm, and careful consideration is given to timing, method, and place of delivery.